2003
DOI: 10.4296/cwrj2804689
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Adaptation Responses of Okanagan River Sockeye Salmon (Oncorhynchus nerka) to Climate Variation and Change Effects During Freshwater Migration: Stock Restoration and Fisheries Management Implications

Abstract: We summarized existing knowledge on behavioural and physiological responses of Okanagan sockeye salmon (O. nerka) adults to annual and seasonal variations in aquatic thermal regimes during migration. This enabled us to identify an underlying set of 'decision rules' as a biophysical model of how temperature mediates en-route delays as a specific element of annual migrations by sockeye salmon. Several sets of results indicate that adult sockeye migrations stop as seasonal water temperatures increase and exceed 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 14 publications
(27 reference statements)
4
60
1
Order By: Relevance
“…The results also suggest an apparent threshold temperature for Columbia River fall Chinook salmon between 208C and 218C, above which many fish seek refugia or reduce migration activity. A similar threshold has been identified for Columbia River sockeye salmon O. nerka (Hyatt et al 2003).…”
Section: Discussionsupporting
confidence: 68%
“…The results also suggest an apparent threshold temperature for Columbia River fall Chinook salmon between 208C and 218C, above which many fish seek refugia or reduce migration activity. A similar threshold has been identified for Columbia River sockeye salmon O. nerka (Hyatt et al 2003).…”
Section: Discussionsupporting
confidence: 68%
“…Multiple studies have shown that migrating adult Pacific salmon will exploit cool water refuge to avoid warmer water temperatures during the freshwater migration, likely to conserve energy and to develop healthy gametes (Berman and Quinn, 1991;Newell and Quinn, 2005;Hyatt et al, 2003;Goniea et al, 2006;Keefer et al, 2009;Mathes et al, 2010). In our study, we found no evidence that the Puntledge River summer-run Chinook salmon were able to find and use cool water refugia, which may indicate that the river is generally well mixed.…”
Section: Cool-water Refugecontrasting
confidence: 83%
“…that anomalously high river temperatures probably contributed to the mortality of millions of migrating salmon in recent years (Fraser 1995;Williams 2005), placing the sustainability of Canada's largest salmon-producing river system in jeopardy (Cooke et al 2004). Such temperature concerns extend beyond the Fraser River to the Columbia River in neighboring Washington, Idaho, and Oregon (Quinn et al 1997), where there are reports of sockeye salmon temporarily ceasing their migration when river temperature increased to 121ЊC after migration had begun (Hyatt et al 2003;Goniea et al 2006;Keefer et al 2007). It has been claimed that no sockeye population in the world has successfully established a river migration period when the historic mean water temperature exceeds 19ЊC (Hodgson and Quinn 2002).…”
Section: Salmon Migration and River Temperaturementioning
confidence: 99%